FUNCTIONAL MODULAR COMPOSITION FOR THE USE OF MEAT PRODUCTS FROM INULIN-CONTAINING RAW MATERIALS - Прилипко, Татьяна; Букалова, Наталья; Богатко, Надежда (SWorldJournal, 2023)
The shortage and high cost of high-quality meat raw materials, on the one hand, and the lack of animal protein in diets, on the other, initiated the emergence and rapid development of a new direction in food production. It consists of a combination of pot